Opposing Transcriptional Mechanisms Regulate Toxoplasma Development - Dong-Pyo Hong (American Society for Microbiology, 2017)
ABSTRACT The Toxoplasma biology that underlies human chronic infection is developmental conversion of the acute tachyzoite stage into the latent bradyzoite stage. We investigated the roles of two alkaline-stress-induced ApiAP2 transcription factors, AP2IV-3 and AP2IX-9, in bradyzoite development. These factors were expressed in two overlapping waves during bradyzoite development, with AP2IX-9 increasing expression earlier than AP2IV-3, which peaked as AP2IX-9 expression was declining. Disruption of the AP2IX-9 gene enhanced, while deletion of AP2IV-3 gene decreased, tissue cyst formation, demonstrating that these factors have opposite functions in bradyzoite development. Conversely, conditional overexpression of FKBP-modified AP2IX-9 or AP2IV-3 with the small molecule Shield 1 had a reciprocal effect on tissue cyst formation, confirming the conclusions of the knockout experiments. The AP2IX-9 repressor and AP2IV-3 activator tissue cyst phenotypes were borne out in gene expression studies that determined that many of the same bradyzoite genes were regulated in an opposite manner by these transcription factors. A common gene target was the canonical bradyzoite marker BAG1, and mechanistic experiments determined that, like AP2IX-9, AP2IV-3 regulates a BAG1 promoter-luciferase reporter and specifically binds the BAG1 promoter in parasite chromatin. Altogether, these results suggest that the AP2IX-9 transcriptional repressor and the AP2IV-3 transcriptional activator likely compete to control bradyzoite gene expression, which may permit Toxoplasma to better adapt to different tissue environments and select a suitable host cell for long-term survival of the dormant tissue cyst. IMPORTANCE Toxoplasma infections are lifelong because of the development of the bradyzoite tissue cyst, which is effectively invisible to the immune system. Despite the important clinical consequences of this developmental pathway, the molecular basis of the switch mechanisms that control tissue cyst formation is still poorly understood. Significant changes in gene expression are associated with tissue cyst development, and ApiAP2 transcription factors are an important mechanism regulating this developmental transcriptome. However, the molecular composition of these ApiAP2 complexes and the operating principles of ApiAP2 mechanisms are not well defined. Here we establish that competing ApiAP2 transcriptional mechanisms operate to regulate this clinically important developmental pathway.